Analisis Respon Konsumen Muslim Terhadap Kedai Kopi Yang Belum Bersertifikat Halal - Dwi Sri Wahyuningsih (CV ODIS, 2021)
A coffee shop is one of the exciting hangout places. However, not every coffee shop has halal certificates, in the Jombang Regency particularly. This study aimed to find Muslim customers’ responses toward coffee shops with no halal certificates in Jombang Regency. The study used a descriptive quantitative method. The result showed that generally, Muslim customers are knowledgeable about halal certificates, but they are less concerned about the existence of halal certificates in coffee shops. Nevertheless, they still have a reservation that makes them more selective in choosing coffee shops, and some of them decide to avoid coffee shops with no halal certificate. Likewise, both Muslim customers and owners support halal certification programs for coffee shops.